Hubungan antara Manusia dengan Tuhan dalam Buku “Seni Merayu Tuhan” Karya Habib Husein Ja’far Al-Hadar (Analisis Hermeneutika Gadamer) - Suhada, Sandy Aji; Mustafa, Mutakhirani; Laely, Nelly Husni (SETYAKI : Jurnal Studi Keagamaan Islam, 2024)
Husein Ja'far Al-Hadar is a moderate Islamic preacher who has the characteristic of preaching like young people in general, namely being easy to get along with and discussing current trends. He is also known as a preacher who can maintain tolerance between religious communities and has a positive impact on all religious adherents who like Habib Ja'far's way of thinking and preaching. In this modern era, people are often careless and forget to increase their spiritualism with the various temptations that exist. So in this case, Habib Ja'far offers us with his book entitled The Art of Seducing God, a guide and reflection for all of us that in the process of getting closer to God we must have the art of seducing Him. There are three problem formulations that will be explained in this thesis, namely the background to writing the book The Art of Seducing God, the pattern of the relationship between humans and God in the book The Art of Seducing God, and Gadamer's thoughts in interpreting a text through this book The Art of Seducing God. So, by using Gadamer's hermeneutics, we can find the meaning of the art of seducing God in question. This research is qualitative research with the type of library research, using the Milles and Haberman analysis method in collecting data. This research uses Gadamer's hermeneutical approach. The result of this research is the book The Art of Seducing God which discusses efforts to seduce God so that we can have religion with love, religion with diversity, religion with God sincerely which was carried out by Habib Ja'far regarding all the problems that exist in this life related to humans and God. . So the key to the art of seducing God is love, sincerity, beauty and servitude. The researcher hopes that with this approach, future research can use other approaches to interpret this book.